An innovative library programme to promote reading culture / Hasniza Amno … [et al.] - Amno, Hasniza; Muhammadan, Lizawati; Azmi, Muhamad Amin; Mansor, Mohamed Hafiz; Shaharuddin, Bakiah (2020)
The Advanced Medical and Dental Institute (AMDI), Universiti Sains Malaysia, is an academic research institute focusing on three core areas; tertiary clinical services, advanced research and postgraduate academic programmes. AMDI is committed to provide healthcare services for the community, especially at the northern region of Malaysia. AMDI library caters for staff and students of the institute, which is a key service centre supporting the main components of AMDI. Books and Coffee Trolley Round is a weekly voluntary programme which is conducted since May 2019. The main objective is to increase the passion for reading as a means of providing valuable knowledge and skills in the community. Besides, this programme also highlights bibliotherapy; which refers to a method of using reading materials to help people with emotional problems, mental illness, or life changing events in their lives. Books and Coffee Trolley programme started off with a "Jom! Derma Buku" campaign where reading materials were donated by the staff and public. We hope to achieve 2,000 reading materials through private and corporate donations to be distributed for FREE during this weekly programme. Initially, two "Free Books Corner" were set up for the pleasure of staff and students of the institute to enhance a reading culture at our institute. Following an intensive effort of collaboration with book publishers, suppliers and private donations, a sufficient number of reading materials were available in our collection which instigated the “Books and Coffee Trolley Round”. During this programme, our volunteers carry a trolley of reading materials along with snacks, tea and coffee. Our volunteers consist of medical specialists, university lecturers, other AMDI/USM staff, cancer survivors, NGO members or the public. A survey was conducted to gauge the response of our clients about the programme. Implementation of this programme has opened for collaboration and linkages within the institute, community, corporate, NGO and individual volunteers to promote reading culture. It has increased our visibility as a healthcare provider as activities were highlighted in our social media. During the rounds, our clients take the opportunity to share their feedback on our services to improve the quality of care that we provide. From a feedback survey among 100 respondents, 63% demonstrated they are “very satisfied” and 35% “satisfied” with this programme. This programme highlights an impactful Library Extension Service that benefits our clients by nurturing reading culture, spirit of goodwill and teamwork. It provides a positive impact to the Institute and materialise the vision and mission of USM.